2012
DOI: 10.1590/s1980-65232012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological contamination of toothbrushes and identification of a decontamination protocol using chlorhexidine spray

Abstract: Purpose: This study evaluated the rate of microbial contamination of toothbrushes used by students and established a protocol for the spraying of 0.12% chlorhexidine to decrease the bacterial presence on the bristles of the brushes.Methods: We performed cultures on selective and nonselective media from toothbrushes used by Dentistry students from State University of West Paraná (Unioeste/PR) to identify and quantify the number of total and specific microorganisms. For the chlorhexidine test, a crossover and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 8 publications
(14 reference statements)
1
26
1
4
Order By: Relevance
“…Results of our study showed that 0.12% chlorhexidine digluconate is effective in decontaminating the toothbrushes, thus supporting the conclusions of the previous studies. 4,11,15 However, in our study, 38% white vinegar and the combination of 38% white vinegar and 3.5% sodium chloride were found to be more efficient.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Results of our study showed that 0.12% chlorhexidine digluconate is effective in decontaminating the toothbrushes, thus supporting the conclusions of the previous studies. 4,11,15 However, in our study, 38% white vinegar and the combination of 38% white vinegar and 3.5% sodium chloride were found to be more efficient.…”
Section: Discussioncontrasting
confidence: 61%
“…It has been well documented in the literature that toothbrushes are excellent locations for the growth of microorganisms, 15 and after each brushing, there is an actual risk of recolonization. 1 Contaminated toothbrushes are the major source of repeated infection of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such barriers are not understood risk to dental health or systemic diseases such as septicemia and gastrointestinal, cardiovascular, respiratory, and renal problems. [3,6,7] For people in developing countries economic barriers have an effect on routinely buying toothbrushes.…”
Section: Introductionmentioning
confidence: 99%
“…Using ultra violate sanitary tools is useful for decontamination of bacteria present in toothbrushes. [6,9] Toothbrushes are often stored in the bathroom or near the toilet and sink and may be exposed to enteric bacteria derived from aerosols. Several supporting factors, including microorganism's defense time, storage conditions, and toothbrush site cause cross infection in the oral cavity [2,10] .…”
Section: Introductionmentioning
confidence: 99%